Clinical management of clubfoot in the ambulatory setting- our 2- year experience with 20 patients - Ana Haidamac; Daniela Craciun; R. Bandac; F. Filip (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
Assessment of conservative treatment using the Ponseti method in children with congenital talipes equino- varus (clubfoot), diagnosed and treated as outpatients in the ambulatory clinic of the County Hospital from Suceava, Romania. Retrospective study over a 2-year tine interval (2021-2023) including children with idiopathic clubfoot who were treated in the Pediatric Surgery Ambulatory Clinic. Demographic information, (age, sex), clinical data related to the TEV and detailed information regarding the treatment using the Ponseti method were analyzed. Only cases of idiopathic clubfoot who entirely received their treatment in our clinic were included in the study. 44 children with clubfoot were identified, of which only 20 (16 boys and 4 girls) met the inclusion criteria; 15 patients had bilateral clubfoot and 5 had unilateral clubfoot. The number of corrective cast immobilizations before Achilles' tendon tenotomy was 4 in 2 children, 5 in 16 children, and 6 in 2 children. Patients were evaluated and monitored by means of the Pirani score, applied at the beginning of treatment and before tenotomy. The tenotomy was followed by cast immobilization for 21 days. Dennis Browne orthosis was subsequently applied. Only one patient abandoned the treatment after applying 5 casts, just before tenotomy. In one patient the equinus correction was incomplete. There were no operative or cast-related complications. The Ponseti method can be performed, with very good results as outpatient treatment. It requires an appropriate trained orthopedic team (orthopedic surgeon, nurse and prosthetic specialist) with experience in carrying out this type of treatment, adequate equipment and compliance from the parents.